2005
DOI: 10.1364/ao.44.007414
|View full text |Cite
|
Sign up to set email alerts
|

Two-color laser-induced incandescence (2C-LII) technique for absolute soot volume fraction measurements in flames

Abstract: A two-color version of the laser-induced incandescence (2C-LII) technique was implemented for measuring absolute soot volume fraction in flames. By using a calibrated tungsten ribbon lamp, soot peak temperatures were measured as a function of fluence at several locations in an ethylene diffusion flame by using a steeply edged laser beam profile. Above a certain fluence threshold, peak temperatures were tightly distributed just above 4000 K independent of the particle size and number density. Radial profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…In [47] soot volume fraction results were plotted for a range of possible E(m) slopes and it was found that soot volume fraction varied from −30% to 65% as the slope of E(m) was varied over a realistic range. De Iullis et al [24] noted the influence of E(m) λ in their data interpretation and inconsistencies between optimal choice for E(m) λ in LII and extinction measurements and suggested the need for a follow up investigation. Liu et al [42] presented a formalized analysis of the sensitivity of soot temperature and concentration from auto-compensating LII and noted a strong dependence of soot volume fraction on E(m) 1 and E(m) 2 .…”
Section: Variable Distribution Parameters Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [47] soot volume fraction results were plotted for a range of possible E(m) slopes and it was found that soot volume fraction varied from −30% to 65% as the slope of E(m) was varied over a realistic range. De Iullis et al [24] noted the influence of E(m) λ in their data interpretation and inconsistencies between optimal choice for E(m) λ in LII and extinction measurements and suggested the need for a follow up investigation. Liu et al [42] presented a formalized analysis of the sensitivity of soot temperature and concentration from auto-compensating LII and noted a strong dependence of soot volume fraction on E(m) 1 and E(m) 2 .…”
Section: Variable Distribution Parameters Unitsmentioning
confidence: 99%
“…The second strategy involves measurement of the temperature of the heated soot in real-time by two-color emission pyrometry [9,[23][24][25]. Since the temperature of the soot is explicitly calculated based on measurements, it is not necessary to reach sublimation temperatures, and thus the diagnostic is less intrusive and less sensitive to in-flame laser attenuation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Twocolor (2C) pyrometry is frequently used for detecting the particle temperature by measuring the ratio of LII signals in two wavelength bands [2][3][4][5][6]. The signal-to-noise ratio (SNR) of LII measurements strongly decreases with signal duration because of the exponential decay of the signal intensity following the initial heat-up of the gas-borne particles with a pulsed laser.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this technique can be further enhanced by using a cavity ringdown setup [14,15]. Another solution for calibration is to use a two-colour LII approach in combination with a calibration lamp [16,17].…”
Section: Introductionmentioning
confidence: 99%